2017
DOI: 10.21608/bvmj.2017.30491
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of some heat treated fish products in Egyptian markets

Abstract: This study was conducted to confirm the bacterial conditions of fish products with E.O.S, and their hazards on public health. A total of 60 samples of fish products represented by smoked: herring and smoked salmon-semi cooked: fish finger and breaded shrimp (15 of each) were collected from different retail markets for bacteriological examination. The average of APC, Coliform, Escherichia coli, Mould & yeast and Staphylococcus aureus counts (log 10 cfu/g) were 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…APC measures the number of bacteria growing aerobically (in the presence of oxygen) and at moderate temperatures (mesophilically) rather than the total number of bacteria present (ICMSF, 1996). The same results were seen by Hassanien et al (2017), as the APC of smoked herring was 4.17 ± 0.12 log cfu/g and 2022), who found that APC in smoked fish was 3.78 (log cfu/g). The bacterial load was found to be higher in the samples of smoked fish, which may have been caused by secondary contamination during handling and storage of the fish in ice made from contaminated water, as well as by inadequate processing conditions for hygiene and sanitation (Hatha et al 1998).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…APC measures the number of bacteria growing aerobically (in the presence of oxygen) and at moderate temperatures (mesophilically) rather than the total number of bacteria present (ICMSF, 1996). The same results were seen by Hassanien et al (2017), as the APC of smoked herring was 4.17 ± 0.12 log cfu/g and 2022), who found that APC in smoked fish was 3.78 (log cfu/g). The bacterial load was found to be higher in the samples of smoked fish, which may have been caused by secondary contamination during handling and storage of the fish in ice made from contaminated water, as well as by inadequate processing conditions for hygiene and sanitation (Hatha et al 1998).…”
Section: Discussionsupporting
confidence: 72%
“…Increased consumption of fish can reduce problems related to malnutrition (anemia in women and obesity), and nutritional deficiencies like iron, zinc, iodine, and vitamin A can be treated (FAO, 2020). Fish, however, is a reservoir for a variety of microorganisms, and unhygienic handling and storage of the product can cause unpleasant odors and contamination with unfavorable microorganisms (Hassanien et al 2017). Fish rotting, which is characterized by the softening of the muscular tissue and the generation of slime and disagreeable odors, has been found to be greatly influenced by microbial action (Eyo, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study recovered a higher percentage of E. coli isolation from smoked herring, which was contrary to the finding of Gupta et al (47), who reported lower incidence (12.96%) from RTE fish products. In Egypt, Hassanien et al (48) isolated E. coli with different percentages of 27% in smoked herring and 33% in breaded shrimp. However, another study revealed lower incidence (10%) of E. coli from oyster, while the peeled shrimp was free from E. coli infection (49).…”
Section: Incidence Of Escherichia Coli In Fast Foodmentioning
confidence: 99%